Peran Pondok Pesantren dalam Diseminasi Nilai-nilai Moderasi beragama untuk kalangan Gen Z: Penelitian - Nor Rochmatul Wachidah; M. Luqmanul Hakim Habibie (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The expansion of digital spaces and contemporary social dynamics has significantly transformed the religious attitudes and practices of Generation Z in Indonesia. While unrestricted access to religious information broadens knowledge, it also carries the risk of producing fragmented, reactive, and intolerant interpretations of religion. In the context of Indonesia’s multicultural society, this condition highlights the urgent need for religious educational institutions that are capable of instilling the values of religious moderation in a contextual and sustainable manner. Islamic boarding schools (pondok pesantren), as long-established institutions deeply rooted in local religious and cultural traditions, occupy a strategic position in disseminating the values of religious moderation to Generation Z. This study aims to analyze the role of pesantren in disseminating religious moderation values and to examine their impact on shaping the religious attitudes and behaviors of Generation Z. Employing a qualitative approach with a descriptive-analytical method, this research is based on literature review, observations, and interviews. The findings indicate that pesantren disseminate religious moderation through curriculum integration, exemplary leadership of religious teachers, communal living practices, strengthening religious literacy, and adaptation to digital spaces. These processes not only foster personal piety but also cultivate social piety, tolerance, and national awareness among Generation Z. Therefore, pesantren function not merely as religious educational institutions, but also as cultural and social actors that contribute significantly to maintaining religious harmony and strengthening social cohesion in Indonesia’s pluralistic society.